Perlindungan Hukum Bagi Investor Terhadap Praktik Kejahatan Insider Trading Pada Pasar Modal di Indonesia - Fadilah Haidar (Jurnal Cita Hukum, 2015)
Abstract: Legal Protection for Investors Against Crime Practice Insider Trading In Stock Market in Indonesia. Legal protection for investors is a matter that is crucial to the survival of the business and investing world, a form of legal protection itself in the form of legal structure and legal substance both of which synergize in providing certainty and legal protection. In the absence of legal protection for investors against the crime of insider trading in the stock market it will create unfair market, the emergence of illicit profit, and untrustable adverse market investors.   Abstrak: Perlindungan Hukum Bagi Investor Terhadap Praktik Kejahatan Insider Trading Pada Pasar Modal di Indonesia. Perlindungan hukum bagi investor merupakan suatu hal yang krusial dalam kelangsungan dunia bisnis dan investasi, wujud dari perlindungan hukum itu sendiri berupa legal structure dan legal substance dimana keduanya saling bersinergi dalam memberi kepastian dan perlindungan hukum. Dengan tidak adanya perlindungan hukum bagi investor terhadap kejahatan insider trading di pasar modal maka akan tercipta unfair market, timbulnya illicit profit, dan untrustable market yang merugikan investor.  DOI: 10.15408/jch.v2i1.2311